HBM4EU E-waste study - HBM4EU E-waste Study Team (2025)
Funding Information: HBM4EU E-Waste Study Team: The HBM4EU e-waste study team consists of Kukka Aimonen l, Lasma Akulova m, Radia Bousoumah n, Argelia Casta\u00F1o o, Adam Clarke p, Adrian Covaci q, Maurice van Dael c, Marta Esteban L\u00F3pez o, Thomas G\u00F6eno c, Martien Graumans c, Ogier Hanser n, Beata Janasik r, Kate Jones p, Laura Komarovska m, Sirpa Laitinen l, Henriqueta Louro s, Carla Martins b, Linda Matisane m, Inese Martinsone m, Rodrigo Moreira u, Darren Musgrove p, Maria-Mirela Ani d, Maria Torres Toda f, Ana Nogueira s, Linda Paegle m, Herm\u00EDnia Pinhal s, Tiina Rantio l, S\u00EDlvia Reis Santos s, Edna Ribeiro t, Joanna R\u00F3g a, Anita Seile m, Marina Silva t, S\u00EDlvia Reis Santos s, Marjo V\u00E4nsk\u00E4 l, Riitta Velin l, C\u00E9lia Ventura j,u and Wojciech Wasowicz r., Affiliations of these authors can be found in Supplementary material S3. Funding Information: This work has received external funding from the European Union\u2019s Horizon 2020 research and innovation program under grant agreement No. 733032 and received co-funding from the author\u2019s organizations and/or Ministries. In addition, the Finnish Work Environment fund provided funding (grant no. 200345). The publication was financed by the Science Development Fund of the Warsaw University of Life Sciences \u2013 SGGW. Publisher Copyright: © 2025 The Author(s)